Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1088/1361-6641/aacd54
|View full text |Cite
|
Sign up to set email alerts
|

Identification of swift heavy ion induced defects in Pt/n-GaN Schottky diodes by in-situ deep level transient spectroscopy

Abstract: In-situ measurements such as deep level transient spectroscopy (DLTS) provide reliable information for the identification of defects in electronic devices. For GaN-based devices exposed to swift heavy ion (SHI) irradiation, in situ DLTS investigations are not reported. The defect characterization of irradiated devices has significant relevance in the reliability testing of devices for space applications, detectors for high energy physics experiments, nuclear radiation environments near reactors and for device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…This may be due to the different growth methods of films adopted and different carrier concentration profiles. The films in the reported data [42] are grown by molecular beam epitaxy (MBE) and has higher carrier concentration (2×10 18 /cm 3 ) compared to our sample (~4×10 16 /cm 3 ) [43,44]. The detailed mechanism of the observed trend of Seebeck coefficient in GaN is affected by defects present and may also involve secondary transport mechanisms [42,45].…”
Section: Resultsmentioning
confidence: 65%
“…This may be due to the different growth methods of films adopted and different carrier concentration profiles. The films in the reported data [42] are grown by molecular beam epitaxy (MBE) and has higher carrier concentration (2×10 18 /cm 3 ) compared to our sample (~4×10 16 /cm 3 ) [43,44]. The detailed mechanism of the observed trend of Seebeck coefficient in GaN is affected by defects present and may also involve secondary transport mechanisms [42,45].…”
Section: Resultsmentioning
confidence: 65%
“…This removes user intervention from the process of rate and peak height determination and is not only the strength of this work but is prominent attribute for both L-DLTS and deep-level Fourier spectroscopy [6,7,23]. SLAP offers another means of characterizing defect spectrum through the sequential use of Equation (10), first under the assumption of a single defect (i.e., i = 1, k = 1), followed by the introduction of more defect species (i.e., k > 1).…”
Section: Etcmentioning
confidence: 99%
“…Semiconductor-based components in harsh environments, such as infrared sensors in space, accumulate electrically active defects due to radiation damage [8][9][10][11][12][13][14]. Such defects act as recombination and charge compensation centers and thereby affect minority carrier lifetime and free carrier concentration, which degrade circuit functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on ion irradiation-induced effects in GaN semiconductor devices have been reported in the literature. Studies on GaN-based electronic devices irradiated by different SHIs have reported the formation of nano-tracks in GaN, development of nano-holes on the GaN surface, and an increase in resistivity of GaN [21][22][23][24]. The ion implantation of GaN by low energy ions reported the doping and amorphization of GaN [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Such damage not only induces micro-structural change, but also leads to a change in electrical properties. Most of the previous studies were performed on low-energy ion implantation and on the swift heavy ion (SHI) irradiation [21,22,[27][28][29][30][31][32][33], but there have been only a few studies reporting on MEI irradiation [34,35]. Therefore, the investigation of the impacts of MEI irradiation on semiconductors and their device properties is important both from a fundamental and technological point of view.…”
Section: Introductionmentioning
confidence: 99%